Uvod v kognitivni trening - Kavcic, Voyko (Psihološka obzorja (Ljubljana), 2021)
Over the past few decades, there has been an increased interest in cognitive training and its use. Cognitive or brain training(CT) is defined as guided training in specific tasks, usually structured, with the intention of improving individuals' cognitive abilities while engaging specific cognitive processes, such as attention, memory processes, executive functioning, information processing, or problem solving. This paper presents basic features of CT. A short description of the historical background of CT is given, followed by a description of basic CT parameters as summarized from a meta-analysis published by Lampit et al. (2014). Computerized CT and its advantages are presented as well. The bulk of the paper is dedicated to a discussion of CT effectiveness with emphasis on effectiveness and duration of CT-associated changes and far transfer (i.e., improvement of those cognitive abilities that were not directly engaged during CT training). Neuroplasticity, the presumptive brain underpinning of CT, is introduced. The final conclusion is that there is still a significant need for additional studies that will investigate the different facets of CT, so as to best ensure effective planning and durable outcomes for CT. In addition, there is a need for studies to investigate the best selection of outcome measures for evaluation of CT eff ectiveness to most clearly demonstrate reliable and valid outcomes. The area of CT, combining important fields, including psychology, neuroscience and other related disciplines, has an optimistic future and can contribute importantly to both the individual and societal level.
Keywords: brain training; cognitive ability; cognitive processes; cognitive psychology; kognitivna psihologija; kognitivni procesi; kognitivni trening; neural prasticity; nevroplastičnost; transfer; transfer (learning)